Pengaruh Electronic Word Of Mouth (E- WOM) Dan Online Customer Review (OCR) Terhadap Keputusan Pembelian: Studi Kasus Produk Skincare Asderma Aesthetic - Alfred Heriman Setio; Umi Fadilah Fatoni; Putri Sevi Agustin (Lembaga Pengembangan Kinerja Dosen, 2024)
The research aims to analyze the effect of the Electronic Word of Mouth and online customer review on Purchasing Decisions for Asderma Skincare products. This type of research is a quantitative descriptive research. The population in this study were Asderma customers who actively purchased Asderma Skincare products online with a sample of 75 respondents. This research was conducted using a survey method through online media by filling out the google form and analyzed using multiple linear regression analysis. The results of the study show that Electronic Word of Mouth and online customer review have a positive and significant effect on the decision on purchasing Asderma skincare products.